SNRIs achieve faster antidepressant effects than SSRIs by elevating the concentrations of dopamine in the forebrain. (15th October 2020) - Li, Jie; Lu, Chen; Gao, Zilong; Feng, Yifan; Luo, Huoqing; Lu, Tangsheng; Sun, Xia; Hu, Ji; Luo, Yanli
Abstract: Major depressive disorder (MDD) is a severe mental disorder with a high disability rate worldwide. Selective serotonin reuptake inhibitors (SSRIs) and serotonin and norepinephrine reuptake inhibitors (SNRIs) are the most common agents for antidepressant use. SSRIs and SNRIs are believed to achieve antidepressant effects through the activation of serotonergic or noradrenergic systems. However, whether the dopaminergic system is involved remains unclear. In our study, a genetically encoded dopamine sensor and in vivo fiber photometry recordings were used to measure the dopamine concentrations in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) after acute intraperitoneal injection of SSRIs or SNRIs. Combined with the behavioral tests, we found that SNRIs increased dopamine concentrations in both the mPFC and the NAc and showed faster antidepressant effects than SSRIs. To verify the enhanced dopamine levels induce the faster antidepressant effects of SNRIs, we employed dopamine receptor antagonists to specifically block the dopaminergic function. The results showed that the faster antidepressant effects of SNRIs were weakened by the dopamine receptor antagonists. Altogether, our study reveals that SNRIs achieve faster antidepressant effects than SSRIs by elevating the dopamine concentrations in the mPFC and the NAc. Our work proposes further mechanisms for the first-line antidepressants, which provides more basis for clinical treatments. This article is part of the special issue on Stress, Addiction and Plasticity. Highlights: SNRIs rather than SSRIs enhance dopamine levels in the mPFC and the NAc. SNRIs induce faster antidepressant effects than SSRIs in the mouse model. Dopamine receptor antagonists abolish the faster antidepressant effects of SNRIs.